Performance of the lithium metal infused trenches in the magnum PSI linear plasma simulator. (4th September 2015) - Fiflis, P.; Morgan, T.W.; Brons, S.; Van Eden, G.G.; Van Den Berg, M.A.; Xu, W.; Curreli, D.; Ruzic, D.N.
Abstract: The application of liquid metal, especially liquid lithium, as a plasma facing component (PFC) has the capacity to offer a strong alternative to solid PFCs by reducing damage concerns and enhancing plasma performance. The liquid-metal infused trenches (LiMIT) concept is a liquid metal divertor alternative which employs thermoelectric current from either plasma or external heating in tandem with the toroidal field to self-propel liquid lithium through a series of trenches. LiMIT was tested in the linear plasma simulator, Magnum PSI, at heat fluxes of up to 3 MW m −2 . Results of these experiments, including velocity and temperature measurements, as well as power handling considerations are discussed, focusing on the 80 shots performed at Magnum scanning magnetic fields and heat fluxes up to 0.3 T and 3 MW m −2 . Comparisons to predictions, both analytical and modelled, are made and show good agreement. Concerns over MHD droplet ejection are additionally addressed.